The role of behavior-related comments in parent–child interactions with the digital audio learning system Tiptoi® - Wildt, Eugenia (Frontiers in Developmental Psychology, 2024)
Introduction Whereas previous research has extensively explored shared reading of both print and digital storybooks, it has paid little attention to hybrid storybook reading. This study aims to address two gaps in the existing literature: First, we investigate the use of a hybrid reading medium, specifically Tiptoi®, in the Digital Home Literacy Environment (DHLE) of young children. Second, we examine parental comments during shared storybook reading, focusing particularly on the purpose of behavior-related comments. Methods We conducted a study involving 40 preschoolers and first graders (aged 4–7 years). Using a survey, we examined the use of Tiptoi® as a hybrid reading medium in children's DHLE. Additionally, we analyzed parent-child interactions during shared reading sessions with Tiptoi® through semi-naturalistic observation. Results Results indicate that children aged 4-7 use Tiptoi® regularly and mostly independently. For parent-child interactions, we found that behavior-related comments typically served to provide instructions, to structure the interaction, and to address the technology itself. Discussion Overall, this study provides valuable insights into the use of Tiptoi® in children's DHLE, and it highlights the importance of parental behavior-related comments in enhancing the practice of reading with hybrid storybooks.